PERUBAHAN SINTESIS DNA HASIL INDUKSI METIL METAKRILAT PADA KULTUR JARINGAN - I. G. A. Wahju Ardani (Faculty of Dentistry, Universitas Indonesia, 2015)
Methyl methracrylate (MMA) is used widely for basic material in dental clinics. One of them is cold curing resin acrylic for orthodontics removable appliance. MMA is potentially to have the character to irritate and give an allergic reaction to oral mucous. Previous study showed that MMA have an effect on mitchondrial dehydrogenase repithelial cells by losing its hydrogen and tight on this enzyme. The influence of cold curing resins acrylic on DNA synthesis of oral mucous epithelial is not known until at present. The purpose of this in-vitro study is to examine the DNA synthesis of fibroblast cells BHK-21 induced MMA. The result of this study is to increase the DNA synthesis from the cell culture induced MMA monomer at an incubation time of 12 and 18 hours. Toxicity of MMA was proved to increase DNA synthesis because DNA has a more sensitive effect as a toxic material may cause a deviation of oral mucous.